High‐speed classification of coherent X‐ray diffraction patterns on the K computer for high‐resolution single biomolecule imaging. (2nd October 2013) - Tokuhisa, Atsushi; Arai, Junya; Joti, Yasumasa; Ohno, Yoshiyuki; Kameyama, Toyohisa; Yamamoto, Keiji; Hatanaka, Masayuki; Gerofi, Balazs; Shimada, Akio; Kurokawa, Motoyoshi; Shoji, Fumiyoshi; Okada, Kensuke; et al.
<x xml:space="preserve">Abstract</x> Single‐particle coherent X‐ray diffraction imaging using an X‐ray free‐electron laser has the potential to reveal the three‐dimensional structure of a biological supra‐molecule at sub‐nanometer resolution. In order to realise this method, it is necessary to analyze as many as 1 × 106 noisy X‐ray diffraction patterns, each for an unknown random target orientation. To cope with the severe quantum noise, patterns need to be classified according to their similarities and average similar patterns to improve the signal‐to‐noise ratio. A high‐speed scalable scheme has been developed to carry out classification on the K computer, a 10PFLOPS supercomputer at RIKEN Advanced Institute for Computational Science. It is designed to work on the real‐time basis with the experimental diffraction pattern collection at the X‐ray free‐electron laser facility SACLA so that the result of classification can be feedback for optimizing experimental parameters during the experiment. The present status of our effort developing the system and also a result of application to a set of simulated diffraction patterns is reported. About 1 × 106 diffraction patterns were successfully classificatied by running 255 separate 1 h jobs in 385‐node mode.